More Math Into LaTeX - Grätzer, George (Springer International Publishing : Imprint: Springer, 2016)
For over two decades, this comprehensive manual has been the standard introduction and complete reference for writing articles and books containing mathematical formulas. If the reader requires a streamlined approach to learning LaTeX for composing everyday documents, Grätzer's © 2014 Practical LaTeX may also be a good choice. In this carefully revised fifth edition, the Short Course has been brought up to date and reflects a modern and practical approach to LaTeX usage. New chapters have been added on illustrations and how to use LaTeX on an iPad. Key features: An example-based, visual approach and a gentle introduction with the Short Course A detailed exposition of multiline math formulas with a Visual Guide A unified approach to TeX, LaTeX, and the AMS enhancements A quick introduction to creating presentations with formulas From earlier reviews: Grätzer's book is a solution. -European Mathematical Society Newsletter   There are several LaTeX guides, but this one wins hands down for the elegance of its approach and breadth of coverage. -Amazon.com, Best of 2000, Editor's choice   A novice reader will be able to learn the most essential features of LaTeX sufficient to begin typesetting papers within a few hours of time... An experienced TeX user, on the other hand, will find a systematic and d etailed discussion of LaTeX features.  -Report on Mathematical Physics   A very helpful and useful tool for all scientists and engineers.  -Review of Astronomical Tools.